Rapid electrochemical detection of COVID-19 genomic sequence with dual-function graphene nanocolloids based biosensor - Ang, Wei Li (2022)
Discovered in December 2019, the Severe Acute Respiratory Syndrome Coronavirus 2 (aka SARS-CoV-2 or 2019-nCoV) has attracted worldwide attention and concerns due to its high transmissibility and the severe health consequences experienced upon its infection, particularly by elderly people. Over 329 million people have been infected till date and over 5.5 million people could not survive the respiratory illness known as COVID-19 syndrome. Rapid and low-cost detection methods are of utmost importance to monitor the diffusion of the virus and to aid in the global fight against the pandemic. We propose here the use of graphene oxide nanocolloids (GONC) as an electroactive nanocarbon material that can act simultaneously as a transducing platform as well as the electroactive label for the detection of 2019-nCoV genomic sequences. The ability of GONC to provide an intrinsic electrochemical signal arising from the reduction of the electrochemically reducible oxygen functionalities present on its surface, allows GONC to be used as a simple and sensitive biosensing platform. Different intrinsic electroactivity of the material was obtained at each step of the genosensing process, starting from the immobilization of a short-stranded DNA probe and followed by the incubation with different concentrations of the target 2019-nCoV DNA strand. Monitoring such variations enabled the quantification of the target analyte over a wide dynamic range between 10−10 and 10−5 M. All in all, this proof-of-concept system serves as a stepping stone for the development of a rapid, sensitive and selective analytical tool for the detection of 2019-nCoV as well as other similar viral vectors. The use of cost-effective electrochemical detection methods coupled with the vast availability and suitability of carbon-based nanomaterials make this sensing system a valid candidate for low-cost and point-of-care analysis.